The growth of knowledge and self-perceived competence during long-term internships: comparing preparatory versus accompanying seminars in teacher education programs - Bauer, Max; Traub, Silke; Kunina-Habenicht, Olga (Frontiers in Education, 2024)
Pedagogical field experiences offer valuable learning opportunities in teacher education programs. While most previous studies have exclusively addressed self-perceived competencies, less is known about the extent to which competence objectively changes during internships. With this in mind, this study aims to examine the development of knowledge on instruction, self-perceived competence, teacher self-efficacy, and their interrelationship during a long-term internship with accompanying or preparatory seminars in educational sciences (N = 275). Results of the study revealed a significant change in self-perceived competence and teacher self-efficacy, but only a minimal change in knowledge. The results also showed that accompanying seminars lead to a substantial increase in knowledge relative to preparatory seminars. Furthermore, it turned out that self-perceived competence and its change are less related to knowledge as an objective measure of competence than future teachers’ self-efficacy. Based on these findings, the results from previous studies on student teaching and its effectiveness need to be interpreted more cautiously.